2018
DOI: 10.1055/s-0037-1610084
|View full text |Cite
|
Sign up to set email alerts
|

Vinylation of Benzylic Amines via C–N Bond Functionalization of Benzylic Pyridinium Salts

Abstract: Cross-couplings of benzylic pyridinium salts and vinylboronic acids or esters have been developed. Via these benzylic pyridinium intermediates, benzylic amines can be engaged in these cross-couplings via C-N bond functionalization. This method boasts mild reaction conditions and excellent tolerance for heteroaryl substituents and a range of functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…A subsequent report from this group has also utilized enantioenriched propargylic ammonium triflates to generate allenes in high ee’s. 55 Additionally, the use of benzylic ammonium salts in cross-coupling reactions has led to the development of alternative activating groups for amines, including pyridinium salts, reported by us 56 and others. 57 Overall, we are excited to have identified a novel mode of C(sp 3 )–N bond activation, which allows for the stereospecific formation of new C–C bonds.…”
Section: C(sp3)–n Bond Activation Of Amine Derivativesmentioning
confidence: 99%
“…A subsequent report from this group has also utilized enantioenriched propargylic ammonium triflates to generate allenes in high ee’s. 55 Additionally, the use of benzylic ammonium salts in cross-coupling reactions has led to the development of alternative activating groups for amines, including pyridinium salts, reported by us 56 and others. 57 Overall, we are excited to have identified a novel mode of C(sp 3 )–N bond activation, which allows for the stereospecific formation of new C–C bonds.…”
Section: C(sp3)–n Bond Activation Of Amine Derivativesmentioning
confidence: 99%
“…8,32 Further research demonstrated that pyridinium salts are able to undergo coupling with boronic acids, thereby allowing for the incorporation of diverse groups into their molecular framework. 33–35 Consequently, several functionalities were introduced via this versatile approach, thus broadening the scope of compounds with potential applications in medicinal chemistry. 36…”
Section: Introductionmentioning
confidence: 99%
“…8,32 Further research demonstrated that pyridinium salts are able to undergo coupling with boronic acids, thereby allowing for the incorporation of diverse groups into their molecular framework. [33][34][35] Consequently, several functionalities were introduced via this versatile approach, thus broadening the scope of compounds with potential applications in medicinal chemistry. 36 This study's main aim is to continue the exploration of the capabilities of pyrylium tetrauoroborate within a mechanochemical setting by deamination and arylation of aryl amide substrates, aryl-CO(sp 2 )-NH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was amenable to the coupling of primary benzylic Katritzky salts as well ( Scheme 3 b) [ 43 ]. Additionally, vinyl boranes and alkylborane reagents, generated in situ by hydroboration of alkenes, participated in XC with Katritzky salts ( Scheme 3 c,d) [ 44 , 45 ]. This strategy has been extended beyond Suzuki-Miyaura reactions to include Negishi XC reactions with alkylzinc reagents ( Scheme 3 e) [ 46 ].…”
Section: Introductionmentioning
confidence: 99%